ANALISIS KEPEMIMPINAN SPIRITUAL DAN KOMUNIKASI ORGANISASIONAL TERHADAP KINERJA KARYAWAN - HERU SULISTYO (Department of Management, Faculty of Economics, Universitas Islam Sutan Agung, Semarang, 2009)
The purpose of this paper is to analyze the influence of spiritual leadership, organizationalcommunication on work’s satisfaction, organizational commitment and work performance ofofficial at Telkom company. The total of this sample study is 100 officials at Telkom Company.The hypothesis is tested by using AMOS Ver.5.0 to get the result of causalities relationbetween developed variable on the model. The result of statistic analysis by using structuralmodel is showing the result of the effect the spiritual leadership gives positive and significantinfluence directly on organizational commitment. The spiritual leadership has no influence onwork satisfaction and work performance. The organizational communication has no influenceon work satisfaction and organizational performance. The organizational communication hasinfluence on work performance. The effect of work satisfaction gives positive and significantinfluence on organizational commitment. The work satisfaction has no influence on work performance.The result of this study to show that organizational commitment influence on performance.Keyword : Spiritual Leadership, Organizational Cummunication, Work Performance